Aqueous Binders Compatible with Ionic Liquid Electrolyte for High‐Performance Aluminum‐Ion Batteries. Issue 22 (14th March 2023) - Yang, Zhaohui; Guo, Meilin; Meng, Pengyu; Jiang, Min; Qiu, Xiangyun; Zhang, Jiao; Fu, Chaopeng
Abstract: The incompatibility of poly(vinylidene difluoride) (PVDF) with acidic ionic liquid electrolytes and the use of toxic and high‐cost N‐methyl pyrrolidone (NMP) solvents hinder the wide application of aluminum‐ion batteries (AIBs). In this work, sodium alginate (Na−Alg) is developed as an aqueous binder for the fabrication of graphite positive electrodes in AIBs. The compatibility of various binders with the ionic liquid electrolyte is evaluated, and interaction between various binders and graphite particles before and after cycling is compared and discussed. The results demonstrate that the well compatibility of Na−Alg in ionic liquids and its reasonable distribution on the graphite surface facilitate fast charge transfer and ion diffusion, reduce electrode polarization, and thus contributing to significantly improved cycling stability and rate capability of AIBs. This work provides a new insight into the development of low‐cost, eco‐friendly, and high‐performance binders for AIBs. Abstract : The suitability of aqueous binders for aluminum ion batteries (AIBs), especially the compatibility with ionic liquids and the distribution on the cathode surface, is systematically investigated. Typically, AIBs with sodium alginate (Na−Alg) as binder exhibit outstanding electrochemical performance in terms of specific capacity, rate capability, and cycling stability.